Assessing parenting capacity in child protection: towards a knowledge‐based model. Issue 3 (13th April 2014) - Houston, Stan
Abstract: The assessment of parenting capacity continues to engender public concern in cases of suspected harm to children. This paper outlines a model for approaching this task based on the application of three key domains of knowledge in social work relating to facts, theory and practice wisdom. The McMaster Model of Family Assessment is identified out of this process and reworked to give it a sharper focus on parenting roles and responsibilities. Seven formative dimensions of parenting are then elicited and combined with an analytical process of identifying strengths, concerns, prospects for growth and impact on child outcomes. The resulting assessment framework, it is argued, adds rigour to professional judgements about parenting capacity and enhances formulations on risk in child protection.